Efficiency of technologies for the use of mineral fertilizers when cultivating spring barley in the forest-steppe of the Middle Volga region - A. A. Artemjev; A. M. Guryanov (Аграрная наука Евро-Северо-Востока, 2023)
In the conditions of the forest-steppe of the Middle Volga region (Republic of Mordovia) there was carried out the research on studying the effect of various technologies for the use of mineral fertilizers, with and without taking into account the intra-soil variability of soil fertility indicators in crops of spring barley of the Zazersky 85 variety. The experiment was carried out in 2012 and 2018 in two fields of grain-row crop rotation on leached chernozem (humus in the 0-25 сm layer – 5.3-6.9 %, nitrate and ammonium nitrogen 6.1-16.8 mg/kg of soil, mobile phosphorus 83-182 mg/kg of soil and exchangeable potassium 90-196 mg/kg of soil). The scheme of the experiment: control (without fertilizers); average dose of fertilizers (N70P34K26 – in 2012, N72P36K25 – in 2018); differentiated dose (N53-80P24-43K17-34 in 2012 and N56-80P25-42K20-27 in 2018). Fertilizer doses are calculated for the planned barley yield of 3.0 t/ha. The experiment was based on the principle of a split plot, where plots of the 1st order were reserved for variants with fertilizers, and plots of the 2nd order (5 plots in each repetition) were used to determine the variability of intra-soil fertility and fertilizer application. On average, for two fields of crop rotation, the highest barley yield (3.14 t/ha) was obtained in the variant with differentiated use of fertilizers, which was significantly 72 % higher than the control and 13 % higher than the variant with average doses. The application of fertilizers taking into account the heterogeneity of nutrients in the soil provided the smallest range of variation in yield (0.8 t/ha) across the plots of the polygon with an insignificant level of variation coefficient (V = 9.8 %). The use of fertilizers in the cultivation of barley had a statistically significant effect on the increase in the weight of 1000 grains, plant height, productive tillering coefficient and ear length. Differentiated doses of fertilizers compared with the averaged doses led to a noticeable increase in the values of productive bushiness of plants (by 8.3 %) and spike length (by 3.9 %). The technology of applying mineral fertilizers, taking into account the intra-soil variability of soil fertility indicators, was distinguished by the highest level of profitability in the production of spring barley grain (47.6 %) compared to traditional (26.2 %) and fertilizer savings (by 7.5-8.5 %).